ANALISIS PENGGUNAAN MEDIA SNOWBALL THROWING TERHADAP KEAKTIFAN DAN PENGUASAAN MUFRADAT SISWA MTSN 3 MATARAM - halimatusadiah, halimatusadiah; Suparmanto, Suparmanto; Afifah, Aghniya; Bidaini, Bidaini (Lugatuna : Jurnal Prodi PBA, 2024)
This study tries to see how the Application of Snowball Throwing Media on the Activeness and Vocabulary Mastery of MTSN 3 Mataram Students, with the aim of knowing the extent of students' activeness and mastery of Arabic vocabulary with the application of learning media in the form of snowball throwing. This study used a qualitative approach with a qualitative descriptive research type. The instruments used were observation and interviews. The results of this study indicate that the snowball throwing media has an effect on the activeness of some students, but it does not have much effect on students' vocabulary mastery.